Paradoks Arus Kas dan Nilai Publik pada BUMD Air Minum - Dominggo Calvino Role Gulu; Syarbini Ikhsan; Gita Desyana (Forum Kerjasama Pendidikan Tinggi, 2026)
Perumdam Tirta Khatulistiwa of Pontianak City recorded solid financial performance during 2022–2024, with net operating cash flow growing from IDR 34.86 billion to IDR 50.62 billion (CAGR +20.50%) and net profit from IDR 23.02 billion to IDR 32.66 billion. However, service quality simultaneously deteriorated: the non-revenue water rate rose from 29.96% to 32.56%, exceeding the national standard of 20%, while adequate water pressure coverage plummeted from 41.84% to 14.71% (CAGR ?40.8%). This study aims to analyze cash allocation patterns and measure their conversion efficiency into public service value using a Critical Case Study approach based on audited financial statements. The analysis shows the Cash Reinvestment Ratio ranged only 4.30%–5.58%, below the 7–11% reference range, while capital expenditure declined (CAGR ?8%) amid strong operating cash growth, indicating that cash surpluses have not been optimally converted into infrastructure investment supporting public service value. These findings confirm that prevailing BUMD performance assessment frameworks (